A Qualitative Study Exploring Family Life in Men Following Neurosurgery for Adult Onset Epileptic Seizures. Issue 2 (27th December 2018) - Raffaele, Martin
Abstract : This study explored family relationship dynamics of men with Adult Onset Epileptic Seizures (AOES) following an elective lobectomy procedure to address their frequent seizure activity. Informants were five Australian men with history of adult-onset epilepsy for which they received neurosurgery (aged 34–59 years). Thematic analysis following semi-structured interviews yielded three themes: role marginalization, role dependency and role enmeshment. All the men reported significant role marginalization in not being consulted about everyday life activities. They also reported to experience decisional role shifting towards their spouses or partners and children post-surgery. Their family role enmeshment experiences included being perceived by spouses or partners as adult–children and by their children as a parent–child. However, some of the men were accepting of these role definitions and to add rather than take away from their health-related quality of life.